Efecto de las altas temperaturas en plantas de interés agrícola de Ecuador y su relación con el cambio climático global. - Vega Cuarán, Sindy Gabriela (2020)
The objective of this research was to know the effects of high temperatures in agricultural plants, how thermal and water stress affects morphological and physiological development. For the experiment, bean plants were used that were subjected to a T1 (35C ° - 40 ° C) and a T2 (40C ° - 45 ° C) for a period of 12 days without water. Corn plants exposed to 3 treatments for 30 days were also used. T1 subjected to (35C ° - 40 ° C), T2 (40C ° - 45 ° C) and a T3 of (45 ° C - 50 ° C) without irrigation. The data were collected at the end of each treatment. For the analysis of the effects, the variables of the height of the plant, the thickness of the stem, the number of leaves and the appearance of the plant were measured, as well as the number and size of the stomata. According to the results, a technical guide was developed that contains the most relevant information found in this research. The analysis of the variables in both bean and corn plants had decreasing results after subjecting them to high temperatures and a water deficit. On the other hand, the evaluation carried out on the bean and corn leaves resulted in an increase in the number of stomata with increasing temperature and the days without irrigation, however in the evaluation corresponding to the length and diameter of stomata it had a result decreasing. Keywords: Heat stress, water stress, climate change, agriculture, food security